Evaluasi Pelaksanaan Pembelajaran Daring Pada Masa Pandemi Covid-19 Di SD Islam Terpadu - Alexon, Alexon; Wachidi, Wachidi; Windayani, Windayani (UNIB Press, 2021)
This research aimed to evaluate the implementation of online learning during the COVID-19 pandemic in terms of the context aspect, Input aspect,Process aspect, and Product aspect. Data collection techniques with online questionnaires through Google Forms and documentation. The samples of this research were 29 teachers, 69 students, and 68 parents from grades 4-6 SDIT Hidayatullah Bengkulu City. The evaluation used the CIPP model and analyzed descriptively quantitatively by calculating the mean. The conclusions of this research were: (1) in terms of context, online learning during the COVID-19 pandemic at SDIT Hidayatullah Bengkulu City was very well done, (2) in terms of input, online learning during the COVID-19 pandemic SDIT Hidayatullah Bengkulu City was well implemented, (3) in terms of Process aspect, online learning during the COVID-19 pandemic SDIT Hidayatullah Bengkulu City was carried out well, (4) in terms of the Product, online learning during the COVID-19 pandemic SDIT Hidayatullah Bengkulu City was quite well done.